An Analysis of Textual Organization and Content of US Abstract Dissertations - rizky lutviana (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2014)
This study attempts to investigating the textual organization and content of US dissertations. The 30 dissertations written by native speaker in the area of teaching are chosen randomly. To come to the conclusion, three steps in analyzing the data are implemented: (1) completing the checklist to identify the content and the order of abstract, (2) calculating the percentage of each abstract element; (3) classifying the finding into three big categorizations, and (4) analyzing the finding. We discover the following findings: (1) the organization of US dissertation abstract follow the linear order of thinking though the content is varied, and (2) there is the essential, less essential, and the non essential components in US abstract dissertation.